A Morphology Studies On Effect Of A Coagulation Bath Mediums As The Phase Inversion Parameter For Poly (Vinylidene Fluoride) (Pvdf) Membranes - A.R. Nurul Izzati; M.D. Irfan Hatim; H Hasbullah; Adil Hatem Rashid (ASEAN Journal of Chemical Engineering, 2016)
In recent years there has been a considerable interest in modifying the PVDF membrane properties to suit with a wide range of applications. However, due to the multivariate nature in membrane fabrication steps, the fabrication techniques remain the key issue. In this article, the uses of different concentration of ethanol in the coagulation bath were investigated as it can improve the hydrophobicity of PVDF membrane and the membrane porous microstructure, i.e. finger-like microstructure. In addition, the coagulation mediums play an important role in determining extended of liquid-liquid demixing/crystallization via an immersion precipitation process. In this study, the effects of coagulation bath mediums on the morphology of PVDF membrane were investigated. Scanning electron microscope (SEM) was used to characterize the membrane microstructure. Octanol was used as a medium to estimate porosity of the membrane by determining the weight of liquid occupied within the membrane pores. The concentration of ethanol in the coagulation bath was varied at 0% until 75% with different evaporation time of 0 and 2 min. The SEM results indicate that the membrane surface porosity changes as ethanol concentration increases. Interestingly, at 0 to 25% ethanol, an asymmetric structure which consists of a dense skin layer accompanied by finger-like structure was formed during membrane casting. The more porous finger-like region which extends towards the skin layer is beneficial for membrane fuctionalization.